Influence of the modifier on the short and long range disorder of stannate perovskites - Alves, Mary C. F.; Souza, Soraia C.; Lima, Hebert H. S.; Nascimento, Marcelo R.; Silva, Maria R. S.; Espinosa, Jose Waldo M.; Lima, Severino J. G.; Longo, Elson [UNESP]; Pizani, P. S.; Soledade, Luiz E. B.; Souza, Antonio G.; Santos, Ieda M. G. (Elsevier B.V. Sa, 2009)
Ca(1-x)Sr(x)SnO(3) powders (x = 0, 0.25,0.50,0.75 and 1) were synthesized by the polymeric precursor method. This method is derived from the Pechini one, being quite simple, yielding a high chemical homogeneity. This work aims at evaluating the influence of the modifier (Sr(2+) and/or Ca(2+)) on the properties of stannates with perovskite structure. The powders were characterized by XRD, Raman and FTIR. The increase of the Sr(2+) concentration in the Ca(1-x)Sr(x)SnO(3) system promotes a high short range organization between the polyhedra, diminishing the high degree of distortions of CaSnO(3) orthorhombic perovskite. on the other hand, it was verified that the samples that with a higher concentration of Ca(2+) show a higher short range organization within the polyhedra (SnO(6)). As a consequence pure SrSnO(3) presents higher long range order, crystallizing at lower temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Crystal structure; Phase transitions; X-ray diffraction; Order-disorder effects